Gut Microbiota as an Epigenetic Regulator: Pilot Study Based on Whole-Genome Methylation Analysis - Himanshu Kumar (American Society for Microbiology, 2014)
ABSTRACT The core human gut microbiota contributes to the developmental origin of diseases by modifying metabolic pathways. To evaluate the predominant microbiota as an epigenetic modifier, we classified 8 pregnant women into two groups based on their dominant microbiota, i.e., Bacteroidetes, Firmicutes, and Proteobacteria. Deep sequencing of DNA methylomes revealed a clear association between bacterial predominance and epigenetic profiles. The genes with differentially methylated promoters in the group in which Firmicutes was dominant were linked to risk of disease, predominantly to cardiovascular disease and specifically to lipid metabolism, obesity, and the inflammatory response. This is one of the first studies that highlights the association of the predominant bacterial phyla in the gut with methylation patterns. Further longitudinal and in-depth studies targeting individual microbial species or metabolites are recommended to give us a deeper insight into the molecular mechanism of such epigenetic modifications. IMPORTANCE Epigenetics encompasses genomic modifications that are due to environmental factors and do not affect the nucleotide sequence. The gut microbiota has an important role in human metabolism and could be a significant environmental factor affecting our epigenome. To investigate the association of gut microbiota with epigenetic changes, we assessed pregnant women and selected the participants based on their predominant gut microbiota for a study on their postpartum methylation profile. Intriguingly, we found that blood DNA methylation patterns were associated with gut microbiota profiles. The gut microbiota profiles, with either Firmicutes or Bacteroidetes as a dominant group, correlated with differential methylation status of gene promoters functionally associated with cardiovascular diseases. Furthermore, differential methylation of gene promoters linked to lipid metabolism and obesity was observed. For the first time, we report here a position of the predominant gut microbiota in epigenetic profiling, suggesting one potential mechanism in obesity with comorbidities, if proven in further in-depth studies.